2012
DOI: 10.3389/fneur.2012.00057
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Sleep Features: Relations to Human Memory Function

Abstract: The recent spread of intracranial electroencephalographic (EEG) recording techniques for presurgical evaluation of drug-resistant epileptic patients is providing new information on the activity of different brain structures during both wakefulness and sleep. The interest has been mainly focused on the medial temporal lobe, and in particular the hippocampal formation, whose peculiar local sleep features have been recently described, providing support to the idea that sleep is not a spatially global phenomenon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 88 publications
(151 reference statements)
1
18
0
Order By: Relevance
“…The presence of hippocampal delta activity during REM sleep as well as wakefulness was also demonstrated by other investigators using stereo-EEG recordings (Moroni et al, 2007Ferrara et al, 2012) while another study reported a phase-locking of single-neuron activity to hippocampal delta activity while patients performed a virtual navigation task (Jacobs et al, 2007). In a recent study we demonstrated a phase-coupling of high-frequency activity with the 1.5-3 Hz mesiotemporal delta oscillations during REM sleep (Clemens et al, 2009).…”
Section: Introductionsupporting
confidence: 78%
“…The presence of hippocampal delta activity during REM sleep as well as wakefulness was also demonstrated by other investigators using stereo-EEG recordings (Moroni et al, 2007Ferrara et al, 2012) while another study reported a phase-locking of single-neuron activity to hippocampal delta activity while patients performed a virtual navigation task (Jacobs et al, 2007). In a recent study we demonstrated a phase-coupling of high-frequency activity with the 1.5-3 Hz mesiotemporal delta oscillations during REM sleep (Clemens et al, 2009).…”
Section: Introductionsupporting
confidence: 78%
“…These are significant changes, as spindles result from interactions of several regions of the brain, including the thalamic reticular nucleus, thalamocortical relay neurons, the hippocampus, and the cortex 25, 26 . During wake, these same circuits are linked to learning, behavioral arousal, and sensory gating 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The epileptogenic focus often originates from the hippocampus and anterior subregions (including the anterior parahippocampal cortex) [2e4], which are areas believed to be involved in both the encoding and consolidation of memory. Memory consolidation is thought to occur through ripples, which are fast frequency discharges (110e300 Hz) interpreted as electric discharges that promote synaptic rearrangement and replay of neural sequences learned during consolidation [5] on the basis of long-term potentiation (LTP) [6,7]. Scalp sleep spindles are believed to represent the cortical equivalent of hippocampal ripples [8,9] and to be a marker of memory consolidation [10e13].…”
Section: Introductionmentioning
confidence: 99%